A new method to estimate load carrying capacity of thin-walled conical shells - Yilmaz, Haluk; Özyurt, Erdem; Tomek, Petr (University of Pardubice, 2018)
The conical shell with different shell thicknesses and base angles at the lower edge are investigated in the study. A new method is proposed to estimate load carrying capacity of the conical shell structures with a base angle less than 25°. The proposed method is also applicable to different radial stiffnesses of the structure. Empirical relationships are established based on the results of the numerical analysis.
Keywords: conical shell; circumferential ring; load carrying capacity; axial loading; FEM